Evolutionary status of T Tauri stars. (August 2018) - Eretnova, Olga; Dudorov, Alexander
Abstract: The problem of determining the masses and ages of T Tauri star (TTS) using their evolutionary status is discussed. We test four pre-main sequence evolutionary models using well determined observational parameters of 12 binary TTSs and two binary red dwarfs. It is shown that the masses derived using the tracks of all models are in good agreement with the masses obtained from the observations of TTSs with masses M > 0.7 M ⊙ (mean error ε ∼ 10%). Low-mass stars with M ≤ 0.7 M ⊙ have significantly greater mean error: ε ∼ 50% for the tracks of Bressan et al. and Chen et al., and ε ∼ 30% for the other tracks. The isochrones of all tested evolutionary models diverge for stars with masses M ≤ 0.7 M ⊙ . The difference increases with the mass decrease and can reach 10% of Kelvin-Helmholtz time for stars with mass M = 0.2 M ⊙ . The ages of most of the considered TTSs are smaller than the Kelvin-Helmholtz time. This confirms their evolutionary status of being pre-main sequence stars.